Komunitas Kicau Mania di Kota Depok dalam Menjalin Solidaritas Anggota - Yohanes Arie; Noviawan Rasyid Ohorella; Choirul Umam (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2020)
Rearing birds is a hobby that develops in the city of Depok. With this hobby, a bird lover community has emerged, one of which is the Chirping Mania Community of Depok. In this community there are many activities, including maintaining and preserving birds and holding exhibitions and competitions which later can also be an economic movement for the surrounding community. Some of these activities are often held to strengthen communication links of their members. The purpose of this study is to describe the communication patterns of the chirping mania depok community in building member solidarity and knowing the factors that influence the chirping mania community depok in maintaining solidarity. The method used in this research is qualitative. Where in this method the researcher used interview, observation, and documentation techniques. Bird enthusiast groups or commonly called chirping mania are increasingly popular nowadays. The rise of chirping context activity indicates the increasing interest in chirping birds also raises conservation awareness for chirping fans. The results of this study indicate that there is a primary communication pattern applied to the chirping mania community in Depok in maintaining solidarity through routine activities such as meetings, joint exercises, chirping birds contests and other social activities. In addition to the primary communication patterns, the Twitter mania community depok also applies a secondary communication pattern that is ongoing contact between members through social media Facebook, WhatsApp, and others.